Pendampingan Masyarakat dalam Pencegahan dan Penanggulangan Bencana Banjir di Kecamatan Candisari Kota Semarang - Ainnur Rahmanti; Syurrahmi Syurrahmi; Abiyasa Farras Lutfian (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Candisari district is one of the urban villages in Semarang City which is prone to flooding and landslides because of its hilly position and lots of cliffs. The party that loses the most when a disaster occurs is the community, so community participation is needed in preventing floods and landslides. This assistance activity begins with increasing the knowledge of residents regarding potential disasters in the Candisari area. The purpose of this activity is to examine community empowerment in flood disaster prevention and management. Increasing empowerment can be done by applying the community empowerment approach, eliminating the inhibiting factors of the empowerment process from an institutional and community capacity perspective and applying the principles of community empowerment. Recommendations from this activity are aimed at several relevant stakeholders such as facilitators, local government and the people of the Candisari Village who are expected to be able to focus on prevention by consulting regarding infrastructure development in the area.